Pengembangan Website untuk Bali Perabot - Murdiaty Murdiaty; Gunawan Ganda; Fandi Halim (Jurnal SIFO Mikroskil, 2015)
Bali Perabot is a trading business that sells various types of furniture, ranging from spring beds, cabinets, and other furniture types. Bali Perabot owner still wants to expand his business. In order to expand the area of marketing, this business has to open branches up to three branches. It surely requires a huge cost and difficult management. The complexity of the business process management is compounded when the store has to serve a lot of customers who do not do transactions, but just merely inquired information about the product that is being sold, especially if it adjacents to several festivals. Based on these problems, Bali Perabot requires a more effective solution in order to expand the marketing scope without having to open many branches and to serve a better information for customers. The solution obtained was to develop a marketing website based on the needs of Bali Perabot owner by using Joomla CMS and is equipped with additional extensions, named VirtueMart 3.0.6.2 and SJ Filter for VirtueMart - Joomla! Module. The developed website has eventually provided convenience to customers who want to search a furniture based on product category, price, and several important specifications needed to determine a product selection.